2005
DOI: 10.1074/jbc.m409823200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Cell Polarity Regulator, a Complex between Atypical PKC and Par6 PB1 Domains

Abstract: A complex of atypical PKC and Par6 is a common regulator for cell polarity-related processes, which is an essential clue to evolutionary conserved cell polarity regulation. Here, we determined the crystal structure of the complex of PKC and Par6␣ PB1 domains to a resolution of 1.5 Å. Both PB1 domains adopt a ubiquitin fold. PKC PB1 presents an OPR, PC, and AID (OPCA) motif, 28 amino acid residues with acidic and hydrophobic residues, which interacts with the conserved lysine residue of Par6␣ PB1 in a front and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 45 publications
6
95
0
Order By: Relevance
“…Together, the electrostatic and hydrogen bond interactions at three paired sites of A1-B1, A2-B2 and A3-B3 within their PB1 domains lead to the formation of stable p62-PKCζ complex. Structural inspections of the reported PB1 homoand hetero-dimers demonstrated that some cognate pairs display auxiliary interactions in addition to the conserved A1-B1 and A2-B2 sites [24,32]. Based on sequence analysis ( Figure 1B), we believe that this additional A3-B3 interface plays a crucial role in the specific recognition between p62 and aPKCs.…”
Section: The Electrostatic Interactions Play a Dominant Role In P62-pmentioning
confidence: 91%
See 4 more Smart Citations
“…Together, the electrostatic and hydrogen bond interactions at three paired sites of A1-B1, A2-B2 and A3-B3 within their PB1 domains lead to the formation of stable p62-PKCζ complex. Structural inspections of the reported PB1 homoand hetero-dimers demonstrated that some cognate pairs display auxiliary interactions in addition to the conserved A1-B1 and A2-B2 sites [24,32]. Based on sequence analysis ( Figure 1B), we believe that this additional A3-B3 interface plays a crucial role in the specific recognition between p62 and aPKCs.…”
Section: The Electrostatic Interactions Play a Dominant Role In P62-pmentioning
confidence: 91%
“…In human genome, there are at least 13 PB1-containing proteins that can form specific homo-or hetero-complexes to precisely modulate cellular signaling pathways, and a number of crystal/NMR structures of the homotypic PB1-PB1 complexes have been reported [24,32,34]. When these PB1 complexes were superimposed to our p62-PKCζ complex, the relative orientations between two interacting PB1 domains in different complexes may change remarkably (Figure 5A).…”
Section: The Apkc-pb1 Domains Belong To Type I Rather Than Type I/iimentioning
confidence: 98%
See 3 more Smart Citations